Lame but loyal ducks - Mariana Lopes da Fonseca (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
This paper analyzes the consequences of an electoral reform introducing mayoral term limits at the municipal level in Portugal. Relying on a difference-in-difference methodology and a novel method that accounts for anticipatory effects of reforms, this study explores variation between and within municipalities to capture the economic and political consequences of limiting the number of consecutive mayoral terms. In contrast to the usual lame duck effect in the literature, I find that term limited mayors decrease current expenditure and reduce both user charges and tax rates. Lame ducks send positive fiscal signals possibly in an attempt to maximize the electoral perspectives and re-election probability of their party in the coming elections. Still, political turnover significantly increases as a result of the electoral reform.
Keywords: D72; H00; H72; 330; reform; politics; incentives